Self-Assembled chitosan/phospholipid nanoparticles: from fundamentals to preparation for advanced drug delivery. (1st January 2020) - Ma, Qingming; Gao, Yang; Sun, Wentao; Cao, Jie; Liang, Yan; Han, Shangcong; Wang, Xinyu; Sun, Yong
Abstract: With the development of nanotechnology, self-assembled chitosan/phospholipid nanoparticles (SACPNs) show great promise in a broad range of applications, including therapy, diagnosis, in suit imaging and on-demand drug delivery. Here, a brief review of the SACPNs is presented, and its critical underlying formation mechanisms are interpreted with an emphasis on the intrinsic physicochemical properties. The state-of-art preparation methods of SACPNs are summarized, with particular descriptions about the classic solvent injection method. Then SACPNs microstructures are characterized, revealing the unique spherical core-shell structure and the drug release mechanisms. Afterwards, a comprehensive and in-depth depiction of their emerging applications, with special attention to drug delivery areas, are categorized and reviewed. Finally, conclusions and outlooks on further advancing the SACPNs toward a more powerful and versatile platform for investigations covering from fundamental understanding to developing multi-functional drug delivery systems are discussed.